The Role of Cooperative in The Milk Value Chain in West Bandung Regency, West Java Province - Y. Resti; R. Baars; M. Verschuur; G. Duteurtre (Media Peternakan, 2017)
The objective of the study was to evaluate the capacity of Northern Bandung Dairy Farmer Cooperative (KPSBU) to support farmers in producing good quality milk within the milk value chain in West Bandung Regency, West Java. The study used qualitative research strategies including desk study, case study, and focus group discussions. The study compared the involvement of three milk collecting actors that were classified into large cooperative (KPSBU), small cooperative (KUD Puspa Mekar), and private company (Bina Kitri Bersama). A total of 18 dairy farmers, 3 milk collecting actors, 2 milk processors, and one livestock officer were interviewed. Three focus group discussions were conducted. The large cooperative performed better in services, milk collection, and milk quality assessment compared to other milk collecting actors. Members’ commitment, inconsistent milk quality, and shortage of good quality fodder were the hindering factors that influenced the collection of good quality milk in the large cooperative. In conclusion, the large cooperative had better performance in service provision, it also had better infrastructures in milk collection and milk quality assessment compared to other milk collecting actors. Increasing the milk quality standard by milk processing companies affected the milk price since 2000.